2001
DOI: 10.1017/s0950268801005234
|View full text |Cite
|
Sign up to set email alerts
|

The seroepidemiology of measles in Western Europe

Abstract: SUMMARYThe European Regional Office of WHO has targeted measles for elimination from the region in 2007. Large national, age and sex stratified serological surveys of measles antibody were conducted in seven Western European countries from 1994-8 as part of the European Seroepidemiology Network. Three patterns were observed in the country-specific measles seroprofiles, ranging from (very) low susceptibility (four countries) to high susceptibility (one country). Susceptibility levels amongst 2-4-year-olds range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
43
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 14 publications
9
43
0
5
Order By: Relevance
“…The overall proportions of patients with protective antibody titers against tetanus, diphtheria, measles, and rubella were compared with the seroprevalence reported for general, age-matched, pediatric populations. [51][52][53][54] The vaccination history indicated that the proportion of vaccinated patients was consistent with the published data on vaccination coverage in agematched populations from low-and intermediate-susceptibility countries in Western Europe. [52][53][54] Analysis of the serum concentrations of specific antibodies revealed seropositivity rates of 94% for tetanus, 89% for diphtheria, 89% for measles, and 84% for rubella, which were comparable to rates reported in literature.…”
Section: Most Frequently Reported Adverse Eventssupporting
confidence: 78%
See 2 more Smart Citations
“…The overall proportions of patients with protective antibody titers against tetanus, diphtheria, measles, and rubella were compared with the seroprevalence reported for general, age-matched, pediatric populations. [51][52][53][54] The vaccination history indicated that the proportion of vaccinated patients was consistent with the published data on vaccination coverage in agematched populations from low-and intermediate-susceptibility countries in Western Europe. [52][53][54] Analysis of the serum concentrations of specific antibodies revealed seropositivity rates of 94% for tetanus, 89% for diphtheria, 89% for measles, and 84% for rubella, which were comparable to rates reported in literature.…”
Section: Most Frequently Reported Adverse Eventssupporting
confidence: 78%
“…[51][52][53][54] The vaccination history indicated that the proportion of vaccinated patients was consistent with the published data on vaccination coverage in agematched populations from low-and intermediate-susceptibility countries in Western Europe. [52][53][54] Analysis of the serum concentrations of specific antibodies revealed seropositivity rates of 94% for tetanus, 89% for diphtheria, 89% for measles, and 84% for rubella, which were comparable to rates reported in literature. [51][52][53][54] Pimecrolimus exposure at the time of vaccination was substantial; the proportion of vaccinated patients who had received pimecrolimus at the time of vaccination was 53% for tetanus and diphtheria (4 doses), 55% for measles, and 47% for rubella.…”
Section: Most Frequently Reported Adverse Eventssupporting
confidence: 78%
See 1 more Smart Citation
“…6,7 These age-specific susceptibility levels could be estimated from high-quality historical vaccine coverage data (but only in populations with no measles transmission) or from population serological surveillance data. 8 Progress towards elimination can also be assessed from age-specific incidence data, but this is less useful when close to elimination because it is possible for susceptible age cohorts to go unnoticed for many years. Outbreaks in older susceptible cohorts have occurred in Europe in recent years and are serious because of the greater morbidity caused by the disease in older individuals.…”
Section: Researchmentioning
confidence: 99%
“…8,12,13 The measles component of the original project included seven countries, and identified four with a low risk of outbreaks (England and Wales, Finland, France and the Netherlands) and three with an intermediate/high risk of measles outbreaks (Denmark, Germany and Italy). Germany and Italy have since experienced outbreaks, highlighting the importance of seroepidemiological surveys and the need for targeted action based on the results.…”
mentioning
confidence: 99%